The Battle for Critical Internet Resources: South America vs. Amazon.com, Inc. - Vargas-Leon, Patricia; Kuehn, Andreas (Law, State and Telecommunications Review, 2015)
Purpose ”“ To analyze the controversy about the allocation of critical Internet resources generated by ICANN's new gTLD program with a particular focus on the .AMAZON TLD. Methodology/approach/design ”“ This article presents an exploratory case study about the .AMAZON controversy. The initial analysis of this ongoing research is based on data collected from various reports and media coverage on ICANN's new gTLD policy. The article draws from political economy theory to analyze disputes about critical Internet resources. Findings ”“ This article discusses preliminary findings of the .AMAZON case, a contested prime example in ICANN's efforts to extend the Internet's domain name space. Practical implications ”“ The findings may inform related controversies in the gTLD program and contribute to a differentiated understanding of CIR allocation in Internet governance, and respective policy-making. Originality/value ”“ The value of this article is the specific discussion of the .AMAZON case in the larger context of ICANN's new gTLD program, and its analysis that describes the controversy from a property rights perspective.